2021
DOI: 10.1038/s41598-021-94682-8
|View full text |Cite
|
Sign up to set email alerts
|

Viscous flow between two sinusoidally deforming curved concentric tubes: advances in endoscopy

Abstract: Viscous flow between two sinusoidally deforming curved concentric tubes is mathematically investigated for the first time. Exact solutions are computed to analyse the flow between these two tubes and graphical outcomes are included for a thorough analysis of the solutions. The present article has prime applications in endoscopy as a novel peristaltic endoscope is introduced first time for a curved sinusoidal tube. This curved nature of outer sinusoidal tube with a flexible peristaltic endoscope placed inside i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…The inner wall of this peristaltic endoscope is sinusoidally deforming and the outer wall of this tube having this endoscope is also sinusoidally deforming wall. This is extension work of the study provided in 24 with heat transfer and thorough entropy interpretation. The equations that interpret this problem are evaluated with the help of Mathematica software and we have availed exact solutions for temperature, entropy, velocity and pressure gradient etc.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The inner wall of this peristaltic endoscope is sinusoidally deforming and the outer wall of this tube having this endoscope is also sinusoidally deforming wall. This is extension work of the study provided in 24 with heat transfer and thorough entropy interpretation. The equations that interpret this problem are evaluated with the help of Mathematica software and we have availed exact solutions for temperature, entropy, velocity and pressure gradient etc.…”
Section: Introductionmentioning
confidence: 71%
“…The sinusoidally fluctuating external wall of the curved tube as well as the internal sinusoidally fluctuating wall of the novel peristaltic endoscope is mathematically considered by following equations given as 15 17 , 24 where has a range between 0 and 1.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…They observed that stress formation in a curve for non-Newtonian parameter is higher than that of viscus case. The mathematical model of viscus fluid flow between a concentric curved tubes is studied by McCash et al 12 Their study mainly related to application in endoscopy. The outcome shows that catheterization can be made more flexible by using a flexible peristaltic endoscope inside a curved sinusoidal tube 13 .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Further analysis of heat transfer has been performed by various researchers by using nanofluids. [21][22][23][24] Not just the physical properties of nanoparticles affect the heat transfer performance of a fluid, the physical appearance of nanoparticles also contributes to both flow characteristics and heat transfer performance of a fluid containing nanoparticles. This was experimentally demonstrated by Timofeeva et al 25 and Xie et al 26 for fluids containing Al 2 O 3 nanoparticles of various shapes.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the nanoparticle framework provides more stability and subsequently refines the biomolecule's physical properties compared with its native state 18–20 . Further analysis of heat transfer has been performed by various researchers by using nanofluids 21–24 …”
Section: Introductionmentioning
confidence: 99%